KOMPARASI PANDANGAN KELOMPOK OPEN THEISM DAN PANDANGAN TEOLOGI REFORMED MENGENAI ALLAH - Grace Son Nassa; Steven Christian Chandra (STAK Reformed Remnant Internasional, 2023)
The purpose of this study is to review and compare the Open Theism and Reformed theology views of God. This research is based on library research and uses the content analysis method. Despite pro-Open Theism optimism that it will help Christians to relate to the transcendent God, when compared with the Reformed theological view of God, it is found that the Open Theism view has the potential to misunderstand the biblical view of God, especially the optimism that humans can change God's decisions. Scripture itself shows that God is independent of Himself. In short, Open Theism's view of God, if returned to an examination of Scripture as Reformed theology does, will find its position is still very subjective and not centered on what the Bible says about God. It is hoped that this research can add insight into the knowledge and character of Christians in addressing the issue of Open Theism.